New Dendrimer-Based Nanoparticles Enhance Curcumin Solubility - Falconieri, Maria Cristina; Adamo, Mauro; Monasterolo, Claudio; Bergonzi, Maria Camilla; Coronnello, Marcella; Bilia, Anna Rita (Planta Medica, 2017)
Curcumin, the main curcuminoid of the popular Indian spice turmeric, is a potent chemopreventive agent and useful in many different diseases. A major limitation of applicability of curcumin as a health promoting and medicinal agent is its extremely low bioavailability due to efficient first pass metabolism, poor gastrointestinal absorption, rapid elimination, and poor aqueous solubility. In the present study, nanotechnology was selected as a choice approach to enhance the bioavailability of the curcuminis. A new polyamidoamine dendrimer (G0.5) was synthesized, characterized, and tested for cytotoxicity in human breast cancer cells (MCF-7). No cytotoxicity of G0.5 was found in the range between 10−3 and 3 × 10−8 M. Consequently, G0.5 was used to prepare spherical nanoparticles of ca. 150 nm, which were loaded with curcumin [molar ratio G0.5/curcumin 1 : 1 (formulation 1) and 1 : 0.5 (formulation 2)]. Remarkably, the occurrence of a single population of nanoparticles having an excellent polydispersity index (< 0.20) was found in both formulations. Formulation 1 was selected to test in vitro drug release because it was superior in terms of encapsulation efficiency (62 %) and loading capacity (32 %). The solubility of curcumin was increased ca. 415 and 150 times with respect to the unformulated drug, respectively, for formulation 1 and formulation 2. The release of curcumin from the nanoparticles showed an interesting prolonged and sustained release profile.
Keywords: Curcuma longa; Zingiberaceae; curcumin; new polyamidoamine dendrimer-based spherical nanoparticles; solubility